EDUCATORS' STRATEGIES IN IMPLEMENTING LEARNING EVALUATION WITH BORDGAME MEDIA IN FIQH SUBJECTS - fahani, maulfi fahrul; Ulum, M.Chadimul; Maghfirah, Khairina (Maliki Interdisciplinary Journal, 2025)
Learning evaluation is an important aspect in measuring the achievement of learning objectives; however, in practice, evaluation in Fiqh subjects often still uses conventional methods that are less engaging and do not actively involve students. This study aims to examine educators’ strategies in implementing learning evaluation using boardgame media in Fiqh subjects as an innovation to improve the quality of evaluation and student engagement. The research method used is qualitative, with data collected through observation, interviews, and documentation involving educators who apply boardgame media in Fiqh learning evaluation. The results show that the use of boardgame media as an evaluation tool can significantly increase students’ motivation, engagement, and learning outcomes. Educators’ strategies that integrate cognitive, affective, and psychomotor aspects in evaluation through boardgames make the evaluation process more holistic and enjoyable. These findings align with cognitive theory and previous research that confirms the effectiveness of game-based media in Fiqh learning.